Investment, Expectations and Uncertainty: Empirical Evidence on the Relevance of Firm Size - Mark J. Koetse; Arno J. van der Vlist; Henri L.F. de Groot (Tinbergen Institute, 2003)
This paper analyses the effect of uncertainty on investment spending. We analyse twotypes of investment, i.e. aggregate investment and investment in energy saving technologies,using subjective evaluations of expectations and uncertainty of Dutch firms in 1997. Weestimate several models distinguishing between small and large firms. The results suggest thatinvestments in energy saving technologies in small firms are largely cost driven, whereas inlarge firms they are an integral part of general investment spending. Furthermore, expectationsand uncertainty have important although different effects on investment spending in small andlarge firms. We find evidence, at least for small firms, that there are important differencesbetween the effects of uncertainty around input and output variables.
Keywords: D81; L25; Q21; 330; Investment; Expectations; Uncertainty; Firm size.; Investitionsrisiko; Betriebsgröße; Energieeinsparung; Schätzung; Niederlande